THE IMPLEMENTATION OF SOCIOCULTURAL-BASED EDUCATION MANAGEMENT AT MTS MILBOS BOGOR - Muflikhun, Muflikhun; Erihadiana, Mohamad; Ihsanda, Numan; Nurjaman, Irman (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2025)
This research aims to analyze the implementation of educational management based on sociocultural values at MTs MILBoS (Maghfirah Islamic Leadership Boarding School) in addressing the challenges of globalization, which threaten the existence of local values. The background of this study includes several issues, such as globalization bringing cultural homogenization, challenges in harmonizing local values with modern education systems, and the lack of a systematic implementation of sociocultural value-based educational management. This study employs a qualitative method with a case study approach, examining five aspects of educational management: curriculum management, school culture, extracurricular activities, transformational leadership, and relationships with local communities. Data were collected through observation, interviews, and document analysis. The findings show that integrating sociocultural values into the curriculum strengthens students' character in terms of religiosity and collective awareness. An inclusive school culture, skill-based extracurricular activities, and visionary leadership foster innovation in educational management. Synergy with local communities further strengthens social empowerment while preserving cultural identity. This study affirms that an educational approach rooted in sociocultural values is effective in shaping a generation that is adaptive and grounded in local traditions, in line with the theory of social constructivism.